An overview of malaysia’s e-commerce initiatives during and after Covid-19 - Amirrudin, Faizatul Akmam; Mohd Shariff, Balqis (Universiti Teknologi MARA, Terengganu, 2022)
Malaysians have been living with COVID-19 for more than two years since it first emerged in late 2019 in Wuhan, China. The killing virus affected the global economy through lockdowns, closing of shops and restaurants, reductions in public transportation usage due to the infection, loss of employment, etc. Nevertheless, the bright side of this pandemic is the accelerating growth of e-commerce. The lockdown around the world, including in Malaysia, has caused consumers to switch from traditional brick-and-mortar outlets to online marketplaces. According to Bernama (2021) the Malaysian e-commerce industry has continued to flourish in 2021, growing at an accelerated pace due to the COVID-19 pandemic, and this in turn has helped many businesses, especially micro, small and medium enterprises (MSMEs), to stay afloat. Current statistics show that the Malaysian e-commerce market grew yearon- year in 2021. At the same time, the number of online shoppers in Malaysia grew by 47% year-on-year, with 14.43 million buying consumer goods online at the start of 2022.